Skills versus luck: Bolivia and its recent bonanza - Rómulo A. Chumacero (Latin American Economic Review, 2019)
This paper uses different approaches to determine the contribution of internal policies and external factors on the good performance of the Bolivian economy in the recent past. It is demonstrated that the extremely favorable external conditions are mainly responsible for its bonanza, and that the domestic policies have, probably, caused more harm, than good. The extent of the harm ranges from 2% to up to 6.1% of GDP per capita.
Keywords: C32; C33; C53; E65; 330; Bolivia; Synthetic control; Panel data; DSGE